Peningkatan Literasi dan Kreativitas Anak di Desa Binuang melalui Program Tematik Literasi - Fajar, Fajar; Fendrik, Muhammad; Huda, Miftahul; Fitriani, Novi Era; Agustra, Yuda; Ashfina, Syarifah Wilda Mairoza; Samosir, Adinda Hapsari Br.; Hayat, Marsya; Wijaya, Marsella Intania; Harahap, Wisnu Prayudha Havana; Zai, Oftafian; Salsabila, Vania Alda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Students from the Thematic Literacy Community Service Program (Kuliah Kerja Nyata/KKN) of Universitas Riau in 2025 conducted literacy program activities at UPT SDN 005 Binuang Village. Literacy is a person's ability to use potential and skills to process and understand information when engaging in reading and writing activities (Ekowati et al., 2019). Through literacy skills, a person not only gains knowledge but can also use their knowledge and experience as capital for the future. The program was implemented at UPT SDN 005 Binuang Village from Monday, July 14, 2025, to Saturday, July 17, 2025. The objective was to improve the literacy of students at UPT SDN 005 Binuang Village through the Literacy Program. The method used involved designing the entire program. Activities began with read-aloud sessions and